Tax law - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2021)
This chapter is divided into three main parts: 1) international tax law, 2) domestic tax law, and 3) tax and regulation. The first part deals with the international tax system and the way it has been affected by technology. This part will focus on income tax. Existing rules of nexus, characterisation of income and treatment of data are increasingly being challenged, leading to changes in the OECD Model Convention and the implementation of the Base Erosion and Profits Shifting (“BEPS”) project. These in turn have had a considerable impact on Singapore tax law, as Singapore is an active participant in these global initiatives. Moving forward, BEPS 2.0 is likely to result in further changes to Singapore tax law.The second part will look at the domestic tax system of Singapore. Technological developments and the digital economy have resulted in changes across most of the major taxes in Singapore, namely, income tax, goods and services tax (“GST”) and stamp duties. For income tax, a key issue is that the “source” of income has become increasingly difficult to determine in the digital economy. For GST, there has been the activation of the Reverse Charge mechanism (for B2B transactions) and the introduction of the Overseas Vendor Registration Regime (“OVRR”) (for B2C transactions). Changes have also taken place in the area of stamp duties, where a system fundamentally built on paper instruments has had to adapt to increasing digitisation of documents and different modes of sending such documents.Finally, the third part will explore the field of tax and regulation, considering how tax law and policy may be used to incentivise and shape behaviour. In particular, it will focus on the key example of automation and adoption of artificial intelligence, showing how Singapore has rejected calls for an automation tax in favour of incentivising the adoption of new technologies.